Creative Togetherness. A Joint-Methods Analysis of Collaborative Artistic Performance - Gesbert, Vincent; Hauw, Denis; Kempf, Adrian; Blauth, Alison; Schiavio, Andrea (Frontiers in Psychology, 2022)
In the present study, we combined first-, second-, and third-person levels of analysis to explore the feeling of being and acting together in the context of collaborative artistic performance. Following participation in an international competition held in Czech Republic in 2018, a team of ten artistic swimmers took part in the study. First, a self-assessment instrument was administered to rate the different aspects of togetherness emerging from their collective activity; second, interviews based on video recordings of their performance were conducted individually with all team members; and third, the performance was evaluated by external artistic swimming experts. By combining these levels of analysis in different ways, we explore how changes in togetherness and lived experience in individual behavior may shape, disrupt, and (re-)stabilize joint performance. Our findings suggest that the experience of being and acting together is transient and changing, often alternating phases of decrease and increase in felt togetherness that can be consistently recognized by swimmers and external raters.